ANALISIS PENANDA KOHESI DALAM WACANA TAJUK RENCANA HARIAN UMUM MERCUSUAR - Marfuah, Julia; Karim, Ali; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
This research aims to describe the use of form anda function of cohesion device in Mercusuar Daily editorial discourse including device of grammatical and lexical cohesion. This research is a qualitative descriptive research. The data collection were done in two ways, namely, (1) refer technique and (2) record technique. Data analysis procedures used trough three stages: (1) data reduction, (2) presentation of data, and (3) conclusion / verivication. Based on the research result, there was the use of devices of grammatical and lexical cohesion in Mercusuar daily editorial discourse of may 2016 edition. Devices used in the grammatical cohesion of discourse include, (1) grammatical  forms of cohesion devices, including : (a) molding (reference), (b) ellipsis (deletion), (c) subtitution, and (d) a conjungtion. Lexical cohesion devices include (a) reps (repetition) that replicated that same right (intact), repeat with replacement, replicated the shape change, repeat with synonym, repeat with hyponym, and (b) collocation. 2) Cohesion devices function as follows : (a) the reference refer to a participant who had been mentioned first in discourse, (b) subtitution serves to replace the spesific language elements with other elements that are interchangeable, (c) ellipsis (deletion). There are some functions that use ellipsis, namely: (1) the effectiveness of the sentence, (2) language efficiency usage, (3) cohesion discourse, (4) to activate the mind of reader or listener  to language which didn’t explicitly disclosed, (5) practicality language, and (d) conjungtion. Conjungtions functions are, (1) the relationship of resistance, (2) stating causality, (3) the relationship extra, (4)the relationship comparison and (5) express a temporal  relationship. The used of lexical cohesion in the form of repetition. Repetition serves to defend the idea of topic being discussed.